Assessing the role of community resilience in marine debris management: Willingness to participate in Nusa Penida marine protected area - Setiawan Sophia Az-Zahro; Suryawan I Wayan Koko; Lee Chun Hung (BIO Web of Conferences)
This exploratory study examines the resilience of the Nusa Penida community in managing marine debris, focusing on how sociodemographic characteristics influence participation in debris management initiatives. A sample of 60 local residents was analyzed to assess the impact of factors such as gender, age, income, education, occupation, and marital status on their willingness to participate (WTP). Using Chi-square statistical analysis, the study revealed that traditional demographic variables did not significantly determine participation levels. Notably, although not reaching conventional statistical significance, occupational differences suggested a trend where specific job roles might influence engagement in environmental activities. This study underscores the importance of understanding community dynamics and resilience in environmental conservation efforts, offering insights that can guide more tailored and effective community engagement strategies.